Thermally conductive silicone composition, cured product, and manufacturing method

By introducing aluminum nitride powder and silicon compounds with specific proportions and particle sizes into the silicone composition, the thermal conductivity and viscosity of the composition are optimized, solving the high-temperature thermal management problem of highly integrated electronic components and providing a heat dissipation solution with excellent insulation and thermal conductivity.

CN123057166APending Publication Date: 2026-11-06SHIN ETSU CHEMICAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202580022825.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-04
Filing Date
2025-03-27
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing thermally conductive silicone compositions have insufficient thermal conductivity in highly integrated electronic components, failing to effectively solve the problem of high-temperature thermal management.

Method used

By introducing spherical aluminum nitride powder and amorphous aluminum nitride powder with specific proportions and particle sizes into an organosilicon composition, and combining it with a silicon compound of specific viscosity, the thermal conductivity and viscosity of the composition are optimized to form a high thermal conductivity organosilicon composition.

Benefits of technology

A high thermal conductivity silicone composition with excellent insulation and thermal conductivity has been developed, which is suitable for heat dissipation components of electronic parts, ensuring effective heat dissipation in high-temperature environments without damaging power devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention provides a thermally conductive organosilicon composition with excellent insulation and thermal conductivity, and moderate viscosity. The thermally conductive organosilicon composition comprises: (A) an organopolysiloxane; and (B) spherical aluminum nitride powder, wherein the oxygen content is less than 0.5% by mass, and the average particle size is 45-85 mm. μ m, ratio (D) 90 / D 10 (a) Amorphous aluminum nitride powder, wherein the BET specific surface area is 1.0~4.0 m². 2 / g, average particle size 0.5~5 μ m; and (D) by the following general formula (1)-SiR 1 a (OR 2 ) 3‑a (1) The silicon compound represented by (B): (C) is 5:5 to 8:2, the total amount of component (B) and component (C) in the composition is 78 to 86% by volume, the above thermally conductive organosilicon composition is 30 to 800 Pa·s, the thermal conductivity is 8.0 W / (m·K) or higher according to the hot disk method according to ISO 22007-2, it has excellent insulation and thermal conductivity, and has a moderate viscosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to silicone compositions with excellent thermal conductivity, and in particular to a silicone composition with excellent insulation properties and high thermal conductivity, as well as its cured form and manufacturing method. When used as a heat dissipation component for electronic parts, it can be installed in electronic devices without damaging heat-generating electronic components such as power devices, transistors, thyristors, and CPUs (central processing units). Background Technology

[0002] In power devices, transistors, thyristors, CPUs, and other heat-generating electronic components, heat removal during operation is a crucial issue. Traditionally, heat dissipation methods typically involve mounting the heat-generating electronic components to heat sinks or metal plates using electrically insulating heat sinks. These heat sinks are typically made of silicone resin containing thermally conductive fillers.

[0003] In recent years, with the increasing integration of circuits within electronic components, the heat generated has also increased. For example, thermal conductivity has become crucial in environments with temperatures above 100°C, especially 150°C. Therefore, materials with higher thermal conductivity than ever before are required. To improve the thermal conductivity of these materials, the most common approach to date has been to incorporate fillers with high thermal conductivity, such as alumina powder or aluminum nitride powder, into the matrix resin (Patent Documents 1 and 2).

[0004] Therefore, in order to improve thermal conductivity, a technical solution for a high thermal conductivity resin composition has been disclosed, specifying an average sphericity, hydroxyl content, and average particle size of 10~50. m Spherical alumina powder with an average particle size of 0.3~1 μm and a specified particle size of 0.3~1 μm. m The formula specifies the mixing ratio and volume ratio of each alumina, but the maximum average particle size of the spherical alumina powder is 50. m At m, there is a problem of insufficient thermal conductivity (Patent Document 3).

[0005] In addition, although the use of an average particle size of 0.1~100 was proposed... m A thermally conductive organosilicon composition of alumina powder with a particle size of 5-50 μm is disclosed, but specific specifications for thermal conductivity and viscosity are not provided. Furthermore, while a thermally conductive organosilicon composition is disclosed, it specifies an average particle size of 5-50 μm. m m (excluding 5) m Spherical alumina powder with an average particle size of 0.1~5 μm and spherical alumina powder with an average particle size of 0.1~5 μm. mThe alumina powder is spherical or amorphous and the mixing ratio and weight ratio of each alumina are specified. However, like Patent Document 5, it does not specify the average sphericity or hydroxyl content of the spherical alumina with a large average particle size, which is insufficient for achieving high thermal conductivity.

[0006] Therefore, a thermally conductive organosilicon composition is proposed, which uses an average sphericity of 0.8 or higher and 30 hydroxyl groups / nm. 2 The following have an average particle size of 50~150 mm. m The spherical alumina powder is m, but there is no specification for the particle size distribution of the spherical alumina powder, which limits the ability to achieve further high thermal conductivity while ensuring flowability (Patent Document 4).

[0007] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2005-162555 Patent Document 2: Japanese Patent Application Publication No. 2005-209765 Patent Document 3: Japanese Patent Application Publication No. 2013-056996 Patent Document 4: International Publication No. 2018 / 088416 Summary of the Invention

[0008] The technical problem that the invention aims to solve The present invention was made in view of the above circumstances, and its object is to provide a thermally conductive silicone composition with excellent insulation and thermal conductivity and moderate viscosity, particularly a thermally conductive silicone composition suitable as a heat dissipation component for electronic parts, as well as the cured product thereof and a method of manufacturing thereof.

[0009] Technical solutions for solving technical problems To achieve the above objectives, the inventors conducted in-depth research and discovered that in an organosilicon composition containing (A) organopolysiloxane, (B) has a specific oxygen content, a specific average particle size, and a ratio (D) 90 / D 10 The present invention comprises (B) spherical aluminum nitride powder within a specific range, (C) amorphous aluminum nitride powder with specific BET specific surface area and average particle size, and (D) a silicon compound containing at least one silyl group in one molecule and having a specific viscosity. By setting the proportions of components (B) and (C) to a specific ratio, the aforementioned problems can be solved, thereby completing the present invention. It should be noted that a curing agent can also be added to this composition to prepare a curable composition.

[0010] Therefore, the present invention provides the following invention.

[0011] 1. A thermally conductive organosilicon composition comprising: (A) Organopolysiloxane (excluding component (D)); (B) Spherical aluminum nitride powder with an oxygen content of less than 0.5% by mass, accumulating to 50% in a volume-based laser diffraction particle size distribution (D). 50 The average particle size is 45~85. m m, and the cumulative total is 90% (D) 90 ) and cumulatively 10% (D 10 The ratio of (D) 90 / D 10 The range is 8 to 12; (C) Amorphous aluminum nitride powder with a BET specific surface area of ​​1.0~4.0 m². 2 / g, average particle size 0.5~5 m m; and (D) A silicon compound containing at least one silyl group represented by the following general formula (1) in one molecule, having a viscosity of 0.01~100 mPa·s at 25°C. -SiR 1 a (OR 2 ) 3-a (1) (where R) 1 R is an unsubstituted or substituted monovalent hydrocarbon group. 2 Independently alkyl, alkoxyalkyl, alkenyl, or acyl, where a is 0, 1, or 2. The volume ratio of component (B) to component (C) is 5:5 to 8:2, and the total volume of component (B) and component (C) in the composition is 78 to 86% by volume. The viscosity of the above-mentioned thermally conductive silicone composition at 25°C is 30~800 Pa·s when measured by a spiral viscometer at a rotation speed of 10 rpm, and the thermal conductivity is 8.0 W / (m·K) or higher according to the hot disk method of ISO 22007-2.

[0012] 2. The thermally conductive organosilicon composition according to 1, wherein component (D) is a silicon compound represented by the following general formula (2). [Chemistry 1]

[0013] (where R) 1 R is an unsubstituted or substituted monovalent hydrocarbon group. 2 Independently alkyl, alkoxyalkyl, alkenyl or acyl, b is an integer from 5 to 100, a is 0, 1 or 2).

[0014] 3. The thermally conductive silicone composition according to 1 or 2, wherein the thermally conductive silicone composition further comprises a curing agent.

[0015] 4. The thermally conductive organosilicon composition according to 3, wherein the thermally conductive organosilicon composition is an addition reaction curing type, a condensation reaction curing type, or an organic peroxide curing type.

[0016] 5. The thermally conductive silicone composition according to claim 4, wherein the thermally conductive silicone composition is an addition-curing type.

[0017] The cured product of the thermally conductive organosilicon composition as described in any one of 6.3 to 5.

[0018] 7. A method for manufacturing the thermally conductive silicone composition according to any one of 1 to 5, comprising a step of mixing components (B) and (C).

[0019] Invention Effects According to the present invention, a high thermal conductivity organosilicon composition with excellent insulation and thermal conductivity and moderate viscosity can be provided. Detailed Implementation

[0020] The present invention will now be described in detail. It should be noted that "thermally conductive organosilicon composition" is sometimes simply referred to as "organosilicon composition".

[0021] [(A) Ingredient] (A) The organopolysiloxane is the main agent of the organosilicon composition of the present invention. Examples of linear alkyl groups bonded to silicon atoms in the organopolysiloxane include: methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecanyl, octadecyl, nonadecanyl, eicosyl, etc.; branched alkyl groups include isopropyl, tert-butyl, isobutyl, 2-methylundecyl, 1-hexylheptyl, etc.; cyclic alkyl groups include cyclopentyl, cyclohexyl, cyclododecyl, etc.; alkenyl groups include vinyl, aryl, butenyl, pentenyl, hexenyl, etc.; aryl groups include phenyl, tolyl, xylyl, etc.; aralkyl groups include benzyl, phenethyl, 2-(2,4,6-trimethylphenyl)propyl, etc.; haloalkyl groups include 3,3,3-trifluoropropyl, 3-chloropropyl, etc.; and hydrogen atoms. Preferably, the atoms are alkyl, alkenyl, aryl, or hydrogen, and more preferably methyl, vinyl, phenyl, or hydrogen.

[0022] (A) The viscosity of the organopolysiloxane at 25°C is not limited, but is preferably 10 to 100,000 mPa·s, more preferably 15 to 50,000 mPa·s, even more preferably 20 to 20,000 mPa·s, and particularly preferably 25 to 10,000 mPa·s. By setting the viscosity above the lower limit mentioned above, the physical properties of the organosilicon composition are further improved, and by setting the viscosity below the upper limit mentioned above, the processability of the organosilicon composition is further improved. It should be noted that the viscosity of each component, such as component (A) and component (D), at 25°C is the value obtained by measuring using a type B viscometer. Based on the viscosity, the rotor, rotation speed, and rotation time are appropriately selected based on conventional methods (hereinafter, the same applies).

[0023] The molecular structure of organopolysiloxanes is not limited, and examples include linear, branched, partially branched linear, and dendritic structures. Among these, linear and partially branched linear structures are preferred. Examples of such organopolysiloxanes include single polymers having these molecular structures, copolymers containing these molecular structures, or mixtures of these polymers.

[0024] More specific examples of organopolysiloxanes include: dimethylvinylsiloxy-terminated dimethyl polysiloxane, methylphenylvinylsiloxy-terminated dimethyl polysiloxane, dimethylvinylsiloxy-terminated dimethyl siloxane-methylphenyl siloxane copolymer, dimethylvinylsiloxy-terminated dimethyl siloxane-methyl vinyl siloxane copolymer, trimethylsiloxy-terminated dimethyl siloxane-methyl vinyl siloxane copolymer, dimethyl(3,3,3-trifluoropropyl) polysiloxane, silanol-terminated dimethyl siloxane-methyl vinyl siloxane copolymer, silanol-terminated dimethyl siloxane-methyl vinyl siloxane-methyl phenyl siloxane copolymer, and (CH3)3SiO 1 / 2 The siloxane unit and formula represented are: (CH3)2(CH2=CH)SiO 1 / 2 The siloxane unit and formula represented by: CH3SiO 3 / 2 The siloxane unit and formula represented by: (CH3)2SiO 2 / 2The following are examples of organosiloxane copolymers with silanol-terminated dimethyl polysiloxanes, silanol-terminated dimethyl siloxane-methylphenyl siloxane copolymers, trimethoxysilyl-terminated dimethyl polysiloxanes, trimethoxysilyl-terminated dimethyl siloxane-methylphenyl siloxane copolymers, methyldimethoxysilyl-terminated dimethyl polysiloxanes, triethoxysilyl-terminated dimethyl polysiloxanes, trimethoxysilylethyl-terminated dimethyl polysiloxanes, dimethylhydrosiloxy-terminated dimethyl polysiloxanes, trimethylsiloxy-terminated dimethyl siloxane-methylhydrosiloxane copolymers, and dimethylhydrosiloxy-terminated dimethyl siloxane-methylhydrosiloxane copolymers, including those with the formula (CH3)3SiO. 1 / 2 The siloxane unit and formula represented by: (CH3)2HSiO 1 / 2 The siloxane unit and formula represented by: SiO 4 / 2 The organosiloxane copolymers represented by the siloxane units can be used alone or in appropriate combinations of two or more.

[0025] When the organosilicon composition is cured by a hydrosilanization reaction, component (A) preferably uses: (AI-1) an organopolysiloxane having an average of more than 0.1 silicon atoms bonded to an alkenyl group in one molecule, and (AI-2) an organohydrogen polysiloxane having at least 2 hydrogen atoms directly bonded to silicon atoms.

[0026] (AI-1) Preferably, it is an organopolysiloxane having an average of 0.5 or more silicon-bonded alkenyl groups per molecule, more preferably an organopolysiloxane having an average of 0.8 or more silicon-bonded alkenyl groups per molecule. This is because if the average number of silicon-bonded alkenyl groups per molecule is less than the lower limit of the above range, the resulting organosilicon composition tends to not cure sufficiently. Examples of silicon-bonded alkenyl groups in this organopolysiloxane include the same alkenyl groups as described above, preferably vinyl groups. Furthermore, examples of silicon-bonded groups other than alkenyl groups in this organopolysiloxane include the same linear alkyl, branched alkyl, cyclic alkyl, aryl, aralkyl, and haloalkyl groups as described above, preferably alkyl and aryl, more preferably methyl and phenyl.

[0027] The (AI-2) component functions as a crosslinking agent. Examples of the groups bonded to silicon atoms in the organohydrogen polysiloxane of (AI-2) include linear alkyl, branched alkyl, cyclic alkyl, aryl, aralkyl, and haloalkyl groups, as described above. Alkyl and aryl groups are preferred, and methyl and phenyl groups are more preferred. The viscosity of the (AI-2) component at 25°C is not limited, but is preferably in the range of 10 to 100,000 mPa·s, more preferably in the range of 15 to 5,000 mPa·s. The molecular structure of the (AI-2) component is not limited, and examples include linear, branched, partially branched linear, cyclic, and dendritic (tree-like) structures. Examples of such organopolysiloxanes include single polymers having these molecular structures, copolymers containing these molecular structures, or mixtures thereof.

[0028] The amount of component (AI-2) is the amount required for curing the organosilicon composition. Specifically, relative to 1 mole of silicon atoms bonded to alkenes in component (AI-1), the amount of silicon atoms bonded to hydrogen atoms in component (AI-2) is preferably in the range of 0.1 to 10 moles, more preferably 0.2 to 5 moles, and even more preferably 0.3 to 3.0 moles. By setting it to the lower limit or above, the effect can be further enhanced; by setting it to the upper limit, the resulting cured organosilicon becomes very hard, preventing the formation of numerous cracks on the surface.

[0029] When the organosilicon composition is cured by a condensation reaction, component (A) is preferably an organopolysiloxane having at least two silanol groups or silicon atom-bonded hydrolyzable groups per molecule (A-II). More preferably, it is an organopolysiloxane having at least two and no more than ten silanol groups or silicon atom-bonded hydrolyzable groups per molecule. Examples of silicon atom-bonded hydrolyzable groups in the organopolysiloxane include: alkoxy groups such as methoxy, ethoxy, and propoxy; alkenoxy groups such as vinyloxy, propoxy, isopropoxy, and 1-ethyl-2-methylvinyloxy; alkoxyalkoxy groups such as methoxyethoxy, ethoxyethoxy, and methoxypropoxy; acyloxy groups such as acetoxy and octyloxy; ketoxime groups such as dimethylketoxime and methylethylketoxime; amino groups such as dimethylamino, diethylamino, and butylamino; aminooxy groups such as dimethylaminooxy and diethylaminooxy; and amide groups such as N-methylacetamido and N-ethylacetamido. In addition, other than the silanol group and the silicon-bonded hydrolyzable group in the organopolysiloxane, the same linear alkyl, branched alkyl, cyclic alkyl, alkenyl, aryl, aralkyl, and haloalkyl groups that are bonded to silicon atoms can be exemplified as described above.

[0030] When the organosilicon composition is cured by a free radical reaction based on an organic peroxide, component (A) is preferably an organopolysiloxane having at least one silicon atom-bonded alkenyl group in one molecule of (A-III). More preferably, it is an organopolysiloxane having an average of 0.1 or more and 20 or less silicon atom-bonded alkenyl groups. Examples of silicon-bonded groups in this organopolysiloxane include linear alkyl, branched alkyl, cyclic alkyl, alkenyl, aryl, aralkyl, and haloalkyl groups as described above, preferably alkyl, alkenyl, and aryl, and more preferably methyl, vinyl, and phenyl.

[0031] (A) The amount of component in the organosilicon composition is preferably 0.4 to 4.0% by mass, more preferably 0.5 to 3.0% by mass.

[0032] [(B) Component] (B) The composition has an oxygen content of less than 0.5% by mass and accumulates to 50% in a volume-based laser diffraction-type particle size distribution. (D) 50 The average particle size is 45~85. m m, and the cumulative percentage is 90% (D) 90 ) and cumulatively 10% (D 10 The ratio of (D) 90 / D 10 The aluminum nitride powder is in the form of 8-12 spherical particles, and can be used alone or in combination of two or more. By using component (B), the thermal conductivity can be further improved while maintaining the flowability of the composition of the present invention.

[0033] The oxygen content of component (B) is 0.5% by mass or less, preferably 0.2% by mass or less. There is no particular limitation on the lower limit; it can be 0.01% by mass or 0% by mass. If the oxygen content, used as a reference for the nitridation rate of component (B), exceeds 0.5% by mass, the crystallite diameter becomes smaller, the chemical purity of component (B) deteriorates, and therefore the thermal conductivity of the composition decreases, potentially leading to poorer thermal properties after moisture resistance. It should be noted that the oxygen content of component (B) can be determined using an oxygen-nitrogen analyzer, analyzed by comparison with silicon nitride in standard data. The "EMGA-920" manufactured by Shimadzu Corporation can be used as the oxygen-nitrogen analyzer.

[0034] In the volume-based laser diffraction-type particle size distribution, the cumulative percentage is 50% (D 50 The average particle size is 45~85. m m, preferably 50~78 m m, more preferably 50~70 m m. It should be noted that if the average particle size is less than 45... m If the average particle size exceeds 85 μm, the resin's filling capacity deteriorates, and the viscosity increases. Conversely, if the average particle size exceeds 85 μm... m m is preferred from the viewpoint of improving the thermal conductivity of the composition, but oil separation is prone to take a long time and the target viscosity cannot be obtained.

[0035] By adjusting the cumulative percentage to 90% (D) 90 ) and cumulatively 10% (D 10 The ratio of (D) 90 / D 10 This allows for a balance between desired viscosity and high thermal conductivity. 90 / D 10 The value is 8-12, preferably 8.5-12.0, more preferably 8.5-11.5, and even more preferably 9-11. If the D in the laser diffraction particle size distribution... 90 / D 10 If D is less than 8, the desired thermal conductivity cannot be obtained; on the other hand, if D... 90 / D 10 If the value exceeds 12, the desired viscosity may not be achieved. Furthermore, D... 90 Preferably 90~250 m m, D 10 Preferably 8~30 m m. If the particle size distribution is wide, then D 90 / D 10 If the particle size distribution is narrow, then D increases. 90 / D 10 It gets smaller.

[0036] From the viewpoint of improving the thermal conductivity of the composition, the BET specific surface area (nitrogen adsorption method) of component (B) is preferably a lower BET specific surface area, preferably 0.3 m². 2 / g or less, more preferably 0.2m 2 / g or less. There is no particular limit to the lower limit of the BET specific surface area, based on the average particle size (D) specified in component (B). 50 The upper limit of ) and the cumulative percentage in the volume-based laser diffraction-type particle size distribution is 90% (D 90 ) and cumulatively 10% (D 10 The ratio of (D) 90 / D 10 (), can be set to 0.05m 2 / g. (B) The BET specific surface area of ​​the component, for example, can be analyzed using "Macsorb (registered trademark) HM Model-1201" manufactured by MOUNTECH.

[0037] (B) The shape of the component is circular. If it is amorphous, the desired viscosity may not be obtained. From the perspective of reducing the initial viscosity of the composition, minimizing viscosity change even after treatment at 200°C, and further improving heat resistance, a circular shape is preferred. It should be noted that in this invention, "circular" refers to a shape with an aspect ratio (average major axis length / average minor axis length) of 2.0 or less, preferably 1.2 to 1.9. The aspect ratio can be measured using dynamic image analysis methods, for example, using the "Dynamic Particle Image Analysis System iSpect DIA-10" manufactured by Shimadzu Corporation.

[0038] (B) Any substance that satisfies the requirements of this invention can be used as the component, and its preparation method is not particularly limited. Examples include reduction nitriding and direct nitriding. From the viewpoint that it is easier to obtain a product with an oxygen content of 0.5% by mass or less, it is preferred to obtain it by direct nitriding. If the substance is obtained by direct nitriding, the chemical purity is improved, thereby further improving the thermal properties after moisture resistance.

[0039] (B) The manufacturing method of the component can be carried out, for example, by a known direct nitriding method (including combustion synthesis), without particular limitation. For example, a method of nitriding metallic aluminum powder alone in a nitrogen atmosphere of 0.2~3 MPa can be cited. Pulverization can also be performed as needed, for example, by a known method such as a ball mill, jet mill, or crusher.

[0040] Furthermore, a method can be described that involves heat-treating component (B) obtained by direct nitriding at 1600–2000 °C in a non-oxidizing atmosphere. This allows angular, amorphous particles to be formed into spherical particles by eliminating their corners, thus making it suitable for reducing the viscosity of the composition. It should be noted that below 1600 °C, it is difficult to achieve spherical shapes, and above 2000 °C, component (B) sinters with each other, resulting in a situation where the desired average particle size cannot be achieved.

[0041] (B) Component is preferably added within a range that does not impair the present invention. Specifically, in order not to significantly reduce the thermal conductivity of the thermally conductive silicone composition, the amount of component (B) is preferably 40 to 70% by volume, more preferably 45 to 65% by volume, relative to the total amount of the silicone composition. By making the amount 40% by volume or more, the thermal conductivity of the silicone composition becomes higher, and by making it 70% by volume or less, the viscosity of the silicone composition can be further suppressed from becoming too high.

[0042] [(C) Component] (C) The composition is BET with a specific surface area of ​​1.0~4.0 m². 2 / g, average particle size 0.5~5 mAmorphous aluminum nitride powder of size m can be used alone or in combination of two or more types. The aspect ratio of the amorphous aluminum nitride powder is not particularly limited, but is preferably 10.0 or less, more preferably 5.0 or less. It should be noted that shapes other than spherical shapes are considered amorphous.

[0043] (C) The BET specific surface area (nitrogen adsorption method) of component (C) is 1.0~4.0 m². 2 / g, preferably 1.1~3.5m 2 / g. If less than 1.0m 2 If the specific surface area exceeds 4.0 m² / g, the surface roughness of the sheet increases, the interfacial thermal resistance increases, and the thermal conductivity decreases. On the other hand, if the specific surface area exceeds 4.0 m² / g... 2 If the particle size is reduced to a certain value (e.g., the contact between particles decreases, leading to a decrease in thermal conductivity due to increased interparticle thermal resistance). The average particle size of component (C) is 0.5~5 g. m m, preferably 0.7~4.8 m m. If less than 0.5 m When the particle diameter exceeds 5 m, the contact between particles decreases, leading to a decrease in thermal conductivity due to increased interparticle thermal resistance. Furthermore, if the diameter exceeds 5 m... m If m is greater, the surface roughness of the sheet increases, the interfacial thermal resistance increases, and the thermal conductivity decreases. It should be noted that the methods for determining the average particle size and BET specific surface area are the same as those for component (B).

[0044] The volume ratio (B):(C) of the above-mentioned component (B):(C) is 5:5 to 8:2, preferably 5:5 to 8.0:2.0, and more preferably 6:4 to 7:3. If the proportion of component (B) is less than 5 by volume (the total of components (B) and (C) is 10, the same applies below), the filling properties of components (B) and (C) may deteriorate. On the other hand, if the proportion of component (B) exceeds 8 by volume, components (B) and (C) are difficult to fill densely, and oil separation may easily occur over time. In addition, the total amount of components (B) and (C) in the composition is 78 to 86% by volume, preferably 79 to 85% by volume, and more preferably 80 to 84% by volume. If the total amount of components (B) and (C) is less than 78% by volume, the desired thermal conductivity cannot be obtained, and if the total amount of components (B) and (C) exceeds 86% by volume, the filling properties may deteriorate.

[0045] [(D) component] (D) is a silicon compound represented by the following general formula (1), and one or more can be used alone or in combination.

[0046] -SiR 1 a (OR 2 ) 3-a(1) (where R) 1 R is an unsubstituted or substituted monovalent hydrocarbon group. 2 Independently alkyl, alkoxyalkyl, alkenyl, or acyl, where a is 0, 1, or 2. Components (B) and (C) are preferably surface treated by (D).

[0047] R 1 The alkyl group is independently unsubstituted or substituted monovalent hydrocarbon group, preferably having 1 to 10 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 3 carbon atoms. Specifically, examples include straight-chain alkyl groups, branched alkyl groups, cyclic alkyl groups, alkenyl groups, aryl groups, aralkyl groups, and haloalkyl groups. Examples of straight-chain alkyl groups include methyl, ethyl, propyl, hexyl, octyl, and decyl. Examples of branched alkyl groups include isopropyl, isobutyl, tert-butyl, and 2-ethylhexyl. Examples of cyclic alkyl groups include cyclopentyl and cyclohexyl. Examples of alkenyl groups include vinyl and aryl. Examples of aryl groups include phenyl and tolyl. Examples of aralkyl groups include 2-phenylethyl and 2-methyl-2-phenylethyl. Examples of haloalkyl groups include 3,3,3-trifluoropropyl, 2-(nonafluorobutyl)ethyl, and 2-(heptadecylfluorooctyl)ethyl. Methyl and phenyl are preferred.

[0048] R 2 It is independently alkyl, alkoxyalkyl, alkenyl, or acyl, preferably alkyl. Examples of alkyl groups include those with R... 1 Examples of alkyl groups include straight-chain alkyl groups, branched alkyl groups, and cyclic alkyl groups. Examples of alkoxyalkyl groups include methoxyethyl and methoxypropyl. Examples of alkenyl groups include those with the same structure as R. 1 The alkenyl group is the same as the alkenyl group shown in the example. The number of carbon atoms is preferably 1 to 8. Examples of acyl groups include acetyl and octanoyl. R 2 Preferably alkyl, more preferably methyl or ethyl.

[0049] As a component (D), (D-1) can be exemplified by organopolysiloxanes represented by the following general formula (2).

[0050] The following general formula (2) [Chemistry 2]

[0051] (where R) 1 R is an unsubstituted or substituted monovalent hydrocarbon group. 2 Independently alkyl, alkoxyalkyl, alkenyl or acyl, b is an integer from 5 to 100, a is 0, 1 or 2) R 1 and R 2Same as above. b is an integer from 5 to 100, preferably from 5 to 50. a is 0, 1, or 2, preferably 0.

[0052] Preferred examples of organopolysiloxanes as components (D-1) include the following organopolysiloxanes.

[0053] [Chemistry 3]

[0054] (In the formula, Me is a methyl group.) When the (D-1) component is incorporated, the amount relative to 100 parts by mass of component (A) is preferably 5 to 1000 parts by mass, more preferably 10 to 900 parts by mass, and even more preferably 20 to 800 parts by mass.

[0055] (D-2) As component (D), (D-2) a silane coupling agent may also be mentioned. Examples of silane coupling agents include vinyl-based silane coupling agents, epoxy-based silane coupling agents, acrylic-based silane coupling agents, and long-chain alkyl-based silane coupling agents, which can be used alone or in combination with component (D-1) or two or more in appropriate combinations. Among these, long-chain alkyl-based silane coupling agents with 5 to 20 carbon atoms are preferred, and decyltrimethoxysilane is more preferred.

[0056] When combined with component (D-2), the amount is preferably 0.05 to 5 parts by mass relative to a total of 100 parts by mass of components (B) and (C), more preferably 0.07 to 4.5 parts by mass, and even more preferably 0.09 to 4 parts by mass. By setting it within the above range, the effect can be further enhanced.

[0057] As a surface treatment method based on components (B) and (C) of component (D), various methods can be employed, including spraying using fluid nozzles, stirring with shear force, dry methods such as ball mills and mixers, and wet methods such as aqueous or organic solvent systems. Stirring is carried out to a degree that does not damage the aluminum nitride powder. In dry methods, the system temperature or the drying temperature after treatment is appropriately determined based on the type of surface treatment agent, within a region where the agent does not volatilize or decompose, for example, 80–180°C.

[0058] (D) The viscosity of the organopolysiloxane at 25°C is 0.01~100 mPa·s, preferably 1~50 mPa·s. If the viscosity is less than 0.01 mPa·s, oil seepage is likely to occur from the organosilicon composition, and it may also sag. If the viscosity exceeds 100 mPa·s, the resulting organosilicon composition will have poor flowability, and the coating workability may deteriorate.

[0059] (D) The amount of component (D) in the organosilicon composition is preferably 2 to 6.5% by mass, more preferably 3 to 6% by mass, and even more preferably 3.5 to 5.5% by mass.

[0060] [Curing composition] The high thermal conductivity organosilicon composition of the present invention can be used directly or further combined with a curing agent to form a curable composition.

[0061] When preparing a curable thermally conductive organosilicon composition, the following three methods can be used as examples. As the base polymer, the organopolysiloxane (A) can be the organopolysiloxane with the above-mentioned components (AI) to (A-IV) combined with the above-mentioned thermally conductive filler materials (B), (C) and (D).

[0062] [I] Addition reaction cured thermally conductive silicone composition [II] Condensation reaction cured thermally conductive silicone composition [III] Organic peroxide-cured thermally conductive silicone composition From the perspective of rapid curing without producing byproducts, [I] addition reaction curing thermally conductive silicone compositions are preferred. Each composition is shown in detail below.

[0063] [I] Addition reaction cured thermally conductive silicone composition In the case where the silicone composition is an addition reaction-cured thermally conductive silicone composition that is cured by a hydrosilylation reaction, the components (AI-1) and (AI-2) shown above are used as (A) above, and the following components are also included, and the curing agent is (E) below.

[0064] (E) Platinum group metal solidification catalyst (F) Addition reaction control agents may be used as needed. (E) Platinum group metal curing catalysts are catalysts used to promote the curing of organosilicon compositions, such as chloroplatinic acid, alcoholic solutions of chloroplatinic acid, platinum olefin complexes, platinum alkenylsiloxane complexes, and platinum carbonyl complexes.

[0065] The amount of component (E) is the amount required for the curing of the silicone composition. Specifically, relative to component (AI-1), the amount of platinum metal in component (F) is preferably 0.01 to 1000 ppm (by mass), more preferably 0.1 to 500 ppm. This is because if the amount of component (F) is less than the lower limit of the above range, the resulting silicone composition may not cure sufficiently. On the other hand, even if the amount exceeds the upper limit of the above range, the curing speed of the resulting silicone composition will not be significantly improved.

[0066] (F) Curing reaction inhibitor To adjust the curing speed of the silicone composition and improve its workability, a curing reaction inhibitor can be used. Examples of curing reaction inhibitors include: acetylene compounds such as 2-methyl-3-butyn-2-ol, 2-phenyl-3-butyn-2-ol, and 1-ethynyl-1-cyclohexanol; ene-yyne compounds such as 3-methyl-3-penten-1-yne and 3,5-dimethyl-3-hexen-1-yne; as well as hydrazine compounds, phosphine compounds, and thiol compounds. One type can be used alone or in appropriate combinations of two or more types.

[0067] (F) The amount of component (F) is not particularly limited, but is preferably 0.0001 to 1.0% by mass relative to the silicone composition. By setting it to the above range, the workability and curing speed of the silicone composition become more suitable.

[0068] [II] Condensation reaction cured thermally conductive silicone composition In the case where the silicone composition is a condensation reaction-cured thermally conductive silicone composition, the (A-II) component shown above is used as (A) above, and the following components are also included, and the curing agent is the following component (G).

[0069] (G)1 Silanes or their partial hydrolysates having at least three silicon-bonded hydrolyzable groups in the molecule. (H) A catalyst for condensation reaction may be used as needed.

[0070] Examples of hydrolyzable groups bonded to the silicon atoms in component (G) include alkoxy, alkoxyalkoxy, acyloxy, ketoxime, alkenoxy, amino, aminooxy, and amide groups, as described above. In addition to the hydrolyzable groups described above, the silicon atoms of this silane may also be bonded to, for example, straight-chain alkyl, branched alkyl, cyclic alkyl, alkenyl, aryl, aralkyl, and haloalkyl groups, as described above. Examples of such silanes or their partial hydrolysates include methyltriethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, and tetraethyl orthosilicate.

[0071] The amount of component (G) is the amount required for the curing of the silicone composition. Specifically, it is preferably 0.01 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, relative to 100 parts by mass of components (A-II). This is because if the content of the silane or its partial hydrolysate is less than the lower limit of the above range, the storage stability of the obtained silicone composition may decrease. On the other hand, if the content exceeds the upper limit of the above range, the curing of the obtained silicone composition may be significantly slower.

[0072] (H) is any component, and is not necessary, for example, when using silanes with hydrolyzable groups such as amino, ketoxime, etc., as curing agents. Examples of catalysts for such condensation reactions include: organotitanates such as tetrabutyl titanate and tetraisopropyl titanate; organotitanium chelates such as diisopropoxybis(acetoacetic acid)titanium and diisopropoxybis(acetoacetate)titanium; organoaluminum compounds such as tri(acetylacetone)aluminum and tri(acetoacetate)aluminum; organoaluminum compounds such as tetra(acetylacetone)zirconium and tetrazirconium butyrate; organotin compounds such as dibutyltin dioctanoate, dibutyltin dilaurate, and butyltin 2-ethylhexanoate; metal salts of organocarboxylic acids such as tin naphthenate, tin oleate, tin butyrate, cobalt naphthenate, and zinc stearate; amine compounds and their salts such as hexylamine and dodecylamine phosphate; quaternary ammonium salts such as benzyltriethylammonium acetate; lower fatty acid salts of alkali metals such as potassium acetate and lithium nitrate; dialkylhydroxylamines such as dimethylhydroxylamine and diethylhydroxylamine; and organosilicon compounds containing guanidine groups.

[0073] When component (H) is included, its amount is sufficient for the curing of the silicone composition. Specifically, it is preferably 0.01 to 20 parts by mass relative to 100 parts by mass of component (A-II), and more preferably 0.1 to 10 parts by mass. This is because, if the catalyst is necessary, and its content is less than the lower limit of the above range, the resulting silicone composition tends to become insufficiently cured. On the other hand, if the content exceeds the upper limit of the above range, the storage stability of the resulting silicone composition tends to decrease.

[0074] [III] Organic peroxide-cured thermally conductive silicone composition When the silicone composition is an organic peroxide-cured thermally conductive silicone composition, the (A-III) component shown above is used as (A) above, and the following components are also included, and the curing agent is the following component (I).

[0075] (I) Organic peroxides Examples of (I) organic peroxides include benzoyl peroxide, dicumyl peroxide, 2,5-dimethylbis(2,5-tert-butylperoxide)hexane, di-tert-butyl peroxide and tert-butyl perbenzoate.

[0076] The amount of component (I) is the amount required for the curing of the silicone composition. Specifically, it is preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the organopolysiloxane of components (A-III) above. If the amount of component (I) is less than the lower limit of the above range, there is a tendency for the obtained silicone composition to become insufficiently cured. On the other hand, even if the amount exceeds the upper limit of the above range, the curing speed of the obtained silicone composition will not be significantly improved, and may instead become the cause of voids.

[0077] Furthermore, in the organosilicon composition of the present invention, other arbitrary components may be included, for example, as fillers such as fumed silica, precipitated silica, and fumed titanium dioxide, or fillers obtained by hydrophobicating the surface of the filler using an organosilicon compound; tackifiers such as 3-epoxypropoxypropyltrimethoxysilane and 3-methacryloyloxypropyltrimethoxysilane; and flame retardant agents and plasticizers such as pigments, dyes, fluorescent dyes, heat-resistant additives, and triazole compounds. It should be noted that, within the scope of not impairing the effects of the present invention, thermally conductive filler materials other than components (B) and (C) may be used, such as aluminum powder, copper powder, silver powder, nickel powder, gold powder, zinc oxide powder, magnesium oxide powder, aluminum oxide powder, boron nitride powder, diamond powder, and carbon powder.

[0078] [Manufacturing Method] The organosilicon composition of the present invention can be prepared by uniformly mixing the given amounts of the components. For example, it is preferable to include a step of mixing components (B) and (C). Furthermore, a step of mixing any components may also be included.

[0079] [Thermoconductive silicone composition] The thermal conductivity of the silicone composition is 8.0 W / (m·K) or higher according to the hot disk method of ISO 22007-2. It is more preferably 9.0 W / (m·K) or higher. There is no particular upper limit; it can be higher, up to 16.0 W / (m·K) or lower. The measurement temperature is 25°C.

[0080] The viscosity at 25°C, when measured using a spiral viscometer at 10 rpm, is 30–800 Pa·s, preferably 30–600 Pa·s, and more preferably 100–400 Pa·s. Within this range, a well-operable organosilicon composition can be obtained.

[0081] [cured material] When the silicone composition is a curable composition, the method for curing it is not limited. Examples include: molding the silicone composition and then leaving it at room temperature; or molding the silicone composition and then heating it to 40-200°C. These methods can yield silicone elastomer molded articles and silicone rubber. Furthermore, the properties of the silicone rubber obtained according to the above methods are not limited; examples include gel-like, low-hardness rubber-like, or high-hardness rubber-like forms. The preferred cured thickness is 150 mm. mm or more. There is no particular upper limit, but considering the size of the heat-generating electronic components using this silicone composition, it is preferably 5 mm or less. It should be noted that when the silicone composition is poured into a molding die with a curing thickness of 6 mm, cured at 100°C for 1 hour, and then measured by pressing a 6 mm thick cured material with a Leeshow OO hardness tester for 30 seconds, the hardness of the cured material is preferably 3 to 90, more preferably 5 to 80, and even more preferably 30 to 80.

[0082] Example Examples and comparative examples are shown to specifically illustrate the present invention, but the present invention is not limited to the following examples. It should be noted that in the following formulas, Me represents methyl, and the bonding order of the siloxane units is not limited. The percentages of composition are by mass unless otherwise specified.

[0083] The components used in the examples and comparative examples are shown below. It should be noted that the viscosities of each component at 25°C are values ​​obtained using a Type B viscometer. Based on the viscosity, the rotor, rotational speed, and rotation time were appropriately selected using conventional methods.

[0084] (A) Ingredients A-1: A dimethyl polysiloxane with a viscosity (25℃) of 400 mPa·s, a specific gravity (25℃) of 0.98, and end-capped with dimethyl vinyl silyl groups, containing 0.018 mol / 100 g of vinyl groups. A-2: A dimethylsiloxane-diphenylsiloxane copolymer with trimethylsiloxy-terminated ends, a molecular chain with a specific gravity (25℃) of 1.07 and a viscosity (25℃) of 400 mPa·s. A-3: A dimethylsiloxane-diphenylsiloxane copolymer with trimethylsiloxy-terminated ends, a molecular chain with a specific gravity (25℃) of 1.00 and a viscosity (25℃) of 1000 mPa·s. A-4: An organohydrogen polysiloxane expressed by the following formula, with a specific gravity (25℃) of 0.97 and a viscosity (25℃) of 28 mPa·s. [Chemistry 4]

[0085] (B) Components Spherical aluminum nitride powder with the properties shown in the table below (specific gravity: 3.32) [Table 1]

[0086] D 90 / D 10 This refers to a cumulative 90% (D) in a volume-based laser diffraction-type particle size distribution. 90 ) and cumulatively 10% (D10 The ratio of ).

[0087] (C) Components Amorphous aluminum nitride powder with a specific gravity of 3.32 exhibiting the properties shown in the table below. [Table 2]

[0088] (D) Component D-1: An organopolysiloxane expressed by the following formula, with a specific gravity (25℃) of 0.97 and a viscosity (25℃) of 30 mPa·s. [Chemistry 5]

[0089] (E) Components E-1: A chloroplatinic acid-1,3-divinyltetramethyldisiloxane complex with a specific gravity (25℃) of 1.00 and a platinum concentration of 1% by mass. (F) Ingredients F-1: A 50% toluene solution of 1-ethynyl-1-cyclohexanol with a specific gravity (25℃) of 0.92. [Example, Comparative Example] Using the above-described components, organosilicon compositions were prepared according to the method shown below, and thermally conductive molded articles were obtained using these organosilicon compositions. They were then evaluated using the method shown below. The results are recorded in a table.

[0090] The above components were mixed in the proportions shown in Tables 3-6 below as follows to obtain an organosilicon composition. Specifically, (A), (B), (C), and (D) were taken in the proportions shown in the table in a 5-liter frame mixer (manufactured by Inoue Manufacturing Co., Ltd., trade name: 5-liter planetary mixer), and mixed under degassing and heating conditions at 150°C for 2 hours. Then, the mixture was cooled to room temperature (25°C), and component (F) was added, and mixed until homogeneous at room temperature (25°C). Component (E) was then added, and the mixture was degassed and mixed until homogeneous at room temperature. The initial viscosity, hardness after curing, and thermal conductivity before and after curing of the organosilicon composition thus obtained were evaluated using the methods shown below. The results are recorded in the table.

[0091] [Initial Viscosity Evaluation] The initial viscosity of the organosilicon composition was measured at 25°C using a Malcom spiral viscometer (model PC-10AA, 10 rpm) after 10 minutes. It should be noted that in Comparative Examples 3 and 9, the oil separation was severe shortly after manufacture, and the viscosity shifted unstablely; therefore, it was determined that the viscosity could not be measured.

[0092] [Hardness Evaluation After Curing] The silicone composition was poured into a mold to achieve a curing thickness of 6 mm and cured at 100°C for 1 hour. The cured product with a thickness of 6 mm was then measured using a Shore OO hardness tester.

[0093] [Thermal conductivity evaluation] The silicone composition was poured into a mold to achieve a curing thickness of 6 mm and cured at 100°C for 1 hour. Then, the thermal conductivity of the resulting 6 mm thick cured product was measured at 25°C using a hot disk method thermophysical property measuring apparatus (TPS 2500 S) manufactured by Kyoto Electronics Industries, Ltd. (according to the hot disk method of ISO 22007-2).

[0094] [Table 3]

[0095] [Table 4]

[0096] [Table 5]

[0097] [Table 6]

Claims

1. A thermally conductive organosilicon composition, characterized in that, Include: (A) Organopolysiloxane, which does not include component (D); (B) Spherical aluminum nitride powder with an oxygen content of less than 0.5% by mass, accumulating to 50% in a volume-based laser diffraction particle size distribution (D). 50 The average particle size is 45~85. μ m, and the cumulative total is 90% (D) 90 ) and cumulatively 10% (D 10 The ratio of (D) 90 / D 10 The range is 8 to 12; (C) Amorphous aluminum nitride powder with a BET specific surface area of ​​1.0~4.0 m². 2 / g, average particle size 0.5~5 μ m; and (D) A silicon compound containing at least one silyl group represented by the following general formula (1) in one molecule, wherein the viscosity of the silicon compound at 25°C is 0.01~100 mPa·s. -SiR 1 a (OR 2 ) 3-a (1) In equation (1), R 1 R is an unsubstituted or substituted monovalent hydrocarbon group. 2 Independently alkyl, alkoxyalkyl, alkenyl, or acyl, where a is 0, 1, or 2. The volume ratio (B):(C) of component (B) is 5:5 to 8:2, and the total volume of component (B) and component (C) in the composition is 78 to 86% by volume. The viscosity of the thermally conductive silicone composition at 25°C is 30~800 Pa·s when measured with a spiral viscometer at 10 rpm, and the thermal conductivity is above 8.0 W / (m·K) according to the hot disk method of ISO 22007-2.

2. The thermally conductive organosilicon composition according to claim 1, wherein, (D) The composition is a silicon compound represented by the following general formula (2), In equation (2), R 1 R is an unsubstituted or substituted monovalent hydrocarbon group. 2 It is independently alkyl, alkoxyalkyl, alkenyl or acyl, b is an integer from 5 to 100, and a is 0, 1 or 2.

3. The thermally conductive organosilicon composition according to claim 1, wherein, The thermally conductive silicone composition also includes a curing agent.

4. The thermally conductive organosilicon composition according to claim 3, wherein, The thermally conductive organosilicon composition is an addition reaction curing type, a condensation reaction curing type, or an organic peroxide curing type.

5. The thermally conductive organosilicon composition according to claim 4, wherein, The thermally conductive organosilicon composition is an addition-reaction cured type.

6. The cured product of the thermally conductive silicone composition according to any one of claims 3 to 5.

7. A method for manufacturing the thermally conductive organosilicon composition according to any one of claims 1 to 5, characterized in that, The process includes mixing components (B) and (C).

Citation Information

Patent Citations

  • Spherical aluminum nitride and its manufacturing method

    JP2005162555A

  • Mixed powder and application thereof

    JP2005209765A

  • High-heat conductive resin composition

    JP2013056996A

  • Thermally conductive silicone composition and cured product thereof, and manufacturing method

    WO2018088416A1